What is new about anticoagulation to ESC 2024 on guideline for Atrial Fibrillation - Ahmed, Chaudhury Meshkat; Sultan, Mohammad Ashraf Uddin (University Heart Journal, 2025)
Thromboembolism is one of the deadly complications of atrial fibrillation (AF). Prevention of thromboembolism is of permanent importance in management of atrial fibrillation. Many a time a clinician has to walk on a thin thread between thromboembolism as hemorrhage. The ESC guideline in 2024 has come up with some important recommendation on use of anticoagulation in prevention of thromboembolism in patients with atrial fibrillation. University Heart Journal 2024; 20(1): 1